Exosomal Cripto-1 Serves as a Potential Biomarker for Perihilar Cholangiocarcinoma - Hu, Chunxiao; Zhang, Yanli; Zhang, Mengjiao; Li, Tingting; Zheng, Xin; Guo, Qining; Zhang, Xin (Frontiers in Oncology, 2021)
Perihilar cholangiocarcinoma (PHCCA) has a poor prognosis, mainly due to diagnosis at an advanced stage. Cripto-1 functions as an oncogene and is highly expressed in several human cancers, however, its clinical application in PHCCA is poorly understood. Herein, we identified that Cripto-1 was released by PHCCA cells via exosomes in vitro and in vivo. Furthermore, an ELISA method was developed to detect exosomal Cripto-1 in the serum of 115 PHCCA patients, 47 cholangitis patients and 65 healthy controls, and it was found that exosomal Cripto-1 was increased in PHCCA patients and associated with metastasis. Compared with traditional serum tumor markers, CA19-9 and CEA, exosomal Cripto-1 demonstrated a larger area under ROC curve for PHCCA diagnosis. The cutoff value of exosomal Cripto-1 was 0.82, achieving a sensitivity of 79.1% and a specificity of 87.5%. As expected, exosomal Cripto-1 levels in immunohistochemically Cripto-1-high cases were significantly elevated compared to in Cripto-1-low cases. When measured 1-week postoperatively, Cripto-1 levels decreased on average from 1.25(0.96-3.26) to 0.85(0.62-1.82). Immunohistochemistry analysis showed Cripto-1 expression was negatively correlated with E-cadherin and was an independent prognostic biomarker for poor survival in PHCCA patients. In conclusion, exosomal Cripto-1 in sera can reflect its expression in the tissue of PHCAA patients and has the potential be a non-invasive biomarker for diagnosis and prognosis of PHCCA.